Substitution and Reduction Reactions Between Some Tetrakis(arylisocyanide)bis(perchlorato)cobalt(II) Complexes and Two Amines: Basicity and Steric Hindrance Effects - A. Oyetunji, Olayinka; D. Paphane, Banyaladzi; A.L. Becker, Clifford (Asian Journal of Chemistry, 2010)
The kinetics of the reactions of two amines, 4-cyanopyridine (4-CNpy) and 4-methylpyridine (4-Mepy) with four tetrakis(arylisocyanide) cobalt(II) complexes, [Co(CNR)4(ClO4)2] {R = 2,6-Me2C6H3 (A), 2,4,6-Me3C6H2 (B), 2,6-Et2C6H3 (C) and 2,6-iPr2C6H3 (D)}, have been studied in 2,2,2-trifluoroethanol medium. The amines reacted with each of the cobalt(II) complexes through an initial fast process, proposed to be substitution of the amine into the coordination sphere of the cobalt(II) complex, followed by a slow process, suggested to be reduction of the substituted Co(II) to Co(I). Each substitution process follows a rate law in which the pseudo first-order rate constant is linearly dependent on the concentration of the amine. Conversely, the subsequent reduction process for each reaction displays saturation kinetics at high amine concentrations. The reaction of each amine with the four Co(II) complexes exhibits significant steric hinderance by arylisocyanides in the order k(A) > k(B) > k(C) > k(D). Comparison of the reactions of 4-CNpy and 4-Mepy with that of pyridine shows that the reaction rate increases with increasing basicity of the amines in the order k(4-CNpy) < k(py) << k(4-Mepy).